Ultrasonic Energy Utilization in Implementation UV Absorbers to Cotton Fabrics - Merdan, Nigar (Asian Journal of Chemistry, 2010)
Clothing provides protection against the ultraviolet radiation emitted by the sun. However the protection provided is not sufficient in some cases. UV absorbers are used to reduce the fiber damage and to reduce fading away colours of dyestuffs fixed in the material caused by UV radiation, as well as those can also be applied especially to the textiles for protecting the people who are being or working in outdoor areas against UV radiation. In this study, the ultrasonic energy sources are utilized in the implementation of UV absorbers to cotton fabrics, based on the cavitation effect of ultrasonic energy it creates in liquid environment. In the study, 100 % cotton woven fabrics have been dyed with Remazol blue RR (DyStar) having 0.2 % colour intensity and after dyeing different concentrations [1, 2, 3 and 4 %] UV absorbers were applied to differently liquored fabrics by conventional ultrasonic probe and ultrasonic bath methodologies. The effects of ultrasonic energy, ultraviolet protection factor values, protection against UV radiation categories and ΔE*, ΔL*, ΔC* and ΔH* colour values and fastness properties were compared in terms of methods.